IMPLEMENTASI KEBIJAKAN BRANDING UNIVERSITAS JEMBER MELALUI MEDIA ONLINE - Makmun, Sukron Makmun; Ardiyanto, Ardiyanto; Wahyudi, Edy (POLITICO, 2018)
AbstractThis research aims to know the Jember University branding policy implementation through online media.Â  This research use descriptive qualitative methods. The primary source of data retrieved from the key informants, including the Rector of the University of Jember, head of public relations and Protocol of the University of Jember, Bureau Chief, and 3 UPTTI. Secondary data sources the study of documents, reports, statistics of the number of students and professors of the University of Jember, data collaboration related to socialization and policies, academic data. The technique of data collection through the reduction of data, interview techniques and technical documentation. The research found that the policy of branding include communication, resources, Disposition, as well as bureaucratic structure has been going according to command policy. Branding through online media includes Brand preference, Brand Recognition and Brand Campaign, involving implementing policies supporting factor mupun online media including websites and applications to build brand perception Universitas Jember as a technology-friendly campus.Keywords: implementation, policy, branding, online media